2020
DOI: 10.37393/jass.2020.02.2
|View full text |Cite
|
Sign up to set email alerts
|

DYNAMICS OF DEVELOPMENT AND EVALUATION OF AGILITY IN SCHOOL EDUCATION (1st-12th GRADE)

Abstract: Physical activity is an important criterion for a healthy lifestyle and a prerequisite for im- proving the motor abilities of adolescents. The aim of this study is to establish the level of development of physical quality agility in all stages of school education. In order to fulfi ll the set aim of the research, we used sports-peda- gogical testing. The research was carried out with 232 pupils from 1st to 12th grade. We used variation analysis and comparative analysis with t-criterion of Student for independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…Molina, Zarzuela, Padilla, Quiñones and Planells, ( 2020) conducted a research study on handball players and found similar results to current study. A study conducted by Tarnichkova, and Petrova (2020) showed contrast results to the present study they found poorer results for pupils in the first two years of high school stage of the secondary educational degree (8th and 9th grade). This shows a low level of development of agility and spatial coordination in this age group.…”
Section: Discussioncontrasting
confidence: 99%
“…Molina, Zarzuela, Padilla, Quiñones and Planells, ( 2020) conducted a research study on handball players and found similar results to current study. A study conducted by Tarnichkova, and Petrova (2020) showed contrast results to the present study they found poorer results for pupils in the first two years of high school stage of the secondary educational degree (8th and 9th grade). This shows a low level of development of agility and spatial coordination in this age group.…”
Section: Discussioncontrasting
confidence: 99%
“…The primary aim of physical education is to develop physical and cardiorespiratory fitness [ 4 ]. Each physical education (PE) lesson should increase physical activity and promote activity and exercises [ 5 ]. CRF is defined as the human body’s circulatory system’s ability to supply fuel and oxygen during sustained physical activity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%